2016
DOI: 10.3345/kjp.2016.59.3.126
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of the Vesikari Scoring System for predicting the viral or bacterial pathogens in pediatric gastroenteritis

Abstract: PurposeTo evaluate the diagnostic value of the Vesikari Scoring System (VSS) as an early predictor of pathogens in children with acute gastroenteritis (AG).MethodsIn this retrospective study, the VSS score, absolute neutrophil count (ANC), and C-reactive protein (CRP) levels were analyzed in 107 hospitalized children with AG, aged 6 months to 17 years. Patients were divided into nonspecific, viral, and bacterial groups according to the pathogens detected using a multiplex polymerase chain reaction (PCR) test.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 13 publications
2
21
1
Order By: Relevance
“…The Vesikari clinical severity scoring system (VCSSS) has been used in clinical trials in assessing rotavirus vaccine efficacy and effectiveness as a tool for defining the primary end point, which is severe rotavirus gastroenteritis [ 11 ]. It has also been used in clinical studies as a measure of acute gastroenteritis severity [ 12 14 ]. The parameters and categories of this severity scale are shown in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…The Vesikari clinical severity scoring system (VCSSS) has been used in clinical trials in assessing rotavirus vaccine efficacy and effectiveness as a tool for defining the primary end point, which is severe rotavirus gastroenteritis [ 11 ]. It has also been used in clinical studies as a measure of acute gastroenteritis severity [ 12 14 ]. The parameters and categories of this severity scale are shown in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…This result is in agreement with previous studies that reported boys are twice more suffered from rotavirus infection than girls and are more likely to be hospitalized. 16 Junaid et al 17 reported that male children excrete rotavirus at a significant higher rate than female children in Nigeria with the ratio 1.8:1. Shim et al 18 also reported that the number of rotavirus infected male was higher the number of rotavirus infected female in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…The Vesikari clinical severity scoring system is the severity scale that was originally developed to evaluate the effectiveness and efficacy of rotavirus vaccines. 16 Recently, the system is used for predicting the viral or non viral pathogens in acute gastroenteritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vesikari Scoring System (VSS) can be considered a useful and reliable infectious marker for pediatric gastroenteritis are enabling development of an early treatment plan and recently verified by many studies [ 16 , 17 ] ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%